IRs PUBLIC DIPLOMACY STRATEGY OF INDONESIA: CASE STUDY INDOMIE GASTROIPLOMACY: public diplomacy - Laode Muhamad Fathun (Kajian Asia Pasifik, 2023)
This paper aims to describe Indonesia's public diplomacy strategy through culinary. Culinary as an instrument of diplomacy. Public diplomacy is an effective instrument to become a communication and investment tool for a country. This study uses a qualitative method based on case studies. This study uses secondary data and literature review data collection techniques. The results found that Indonesia carried out gastrodiplomacy using Indomie which was produced by PT. Indofood Tbk. Gastrodiplomacy was carried out by Indonesia to Nigeria because it saw an opportunity for a financial crisis in that country. Thus, Indomie can become one of the staple foods used by Nigerian people to maintain the stability of human security in the country. And Indonesia's strategy through 3 C + I. Indonesia uses listening, and advocacy, cultural exchange methods to achieve the expected targets and marketing in Nigeria.